Europe and Central Asia Country Risk Profiles for Floods and Earthquakes - World Bank Group (World Bank, Washington, DC, 2017)
The Europe and Central Asia (ECA) Country Risk Profiles for floods and earthquakes presented in this publication are based on quantitative risk assessments derived using global flood and earthquake models.Flood and earthquake risk were defined in terms of affected population and affected gross domestic product (GDP). Earthquake risk was quantified in terms of fatalities and capital loss. Estimates of future population and GDP affected by earthquakes vary significantly among five shared socioeconomic pathways (SSPs) used to represent population and GDP in 2030 and 2080. The objectives are to inform governments of the levels of risk their countries face and facilitate discussions on how they can become more resilient to both and current risks.